Middle Childhood Attachment Strategies: validation of an observational measure. Issue 5 (3rd September 2018) - Brumariu, Laura E.; Giuseppone, Kathryn R.; Kerns, Kathryn A.; Van de Walle, Magali; Bureau, Jean-François; Bosmans, Guy; Lyons-Ruth, Karlen
ABSTRACT: The purpose of this study was to assess behavioral manifestations of attachment in middle childhood, and to evaluate their relations with key theoretical correlates. The sample consisted of 87 children (aged 10–12 years) and their mothers. Dyads participated in an 8-min videotaped discussion of a conflict in their relationships, later scored with the Middle Childhood Attachment Strategies Coding System (MCAS) for key features of all child attachment patterns described in previous literature (secure, ambivalent, avoidant, disorganized-disoriented, caregiving/role-confused, hostile/punitive). To assess validity, relations among MCAS dimensions and other measures of attachment, parenting, and psychological adjustment were evaluated. Results provide preliminary evidence for the psychometric properties of the MCAS in that its behaviorally assessed patterns were associated with theoretically relevant constructs, including maternal warmth/acceptance and psychological control, and children's social competence, depression, and behavioral problems. The MCAS opens new grounds for expanding our understanding of attachment and its outcomes in middle childhood.